Penyelesaian Soal Cerita Siswa Sekolah Dasar Berdasarkan Gender - Muhammad Ilman Nafi'an (Jurnal Absis: Jurnal Pendidikan Matematika dan Matematika, 2021)
This study aimed to describe the ability of students to solve gender assessment questions in elementary schools. This type of research is a descriptive study with a qualitative approach. This research was conducted at SD Quins Tulungagung. Determination of the subject based on gender. The instruments used were the story question test and interview. The data analysis carried out in this study included: (1) reduction, (2) exposure, and (3) interesting about the students' ability to solve story problems in terms of gender in elementary schools. Based on the results of this study, it shows that in solving story problems, male students tend to be better in terms of reasoning because they can carry out problem-solving starting from understanding the questions to evaluating the answers obtained. Then female students who have more accuracy in solving story problems are better than male students.